On the importance of investigating CME complexity evolution during interplanetary propagation - Winslow, Réka M.; Scolini, Camilla; Jian, Lan K.; Nieves-Chinchilla, Teresa; Temmer, Manuela; Carcaboso, Fernando; Schmieder, Brigitte; Poedts, Stefaan; Lynch, Benjamin J.; Wood, Brian E.; Palmerio, Erika; Lugaz, Noé; et al. (Frontiers in Astronomy and Space Sciences, 2022)
This perspective paper brings to light the need for comprehensive studies on the evolution of interplanetary coronal mass ejection (ICME) complexity during propagation. To date, few studies of ICME complexity exist. Here, we define ICME complexity and associated changes in complexity, describe recent works and their limitations, and outline key science questions that need to be tackled. Fundamental research on ICME complexity changes from the solar corona to 1 AU and beyond is critical to our physical understanding of the evolution and interaction of transients in the inner heliosphere. Furthermore, a comprehensive understanding of such changes is required to understand the space weather impact of ICMEs at different heliospheric locations and to improve on predictive space weather models.